Cheminformatics-based identification of phosphorylated RET tyrosine kinase inhibitors for human cancer - Talukder, Md. Enamul Kabir; Aktaruzzaman, Md.; Siddiquee, Noimul Hasan; Islam, Sabrina; Wani, Tanveer A.; Alkahtani, Hamad M.; Zargar, Seema; Raihan, Md. Obayed; Rahman, Md. Mashiar; Pokhrel, Sushil; Ahammad, Foysal (Frontiers in Chemistry, 2024)
Background: RET (rearranged during transfection), an oncogenic protein, is associated with various cancers, including non-small cell lung cancer (NSCLC), papillary thyroid cancer (PTC), pancreatic cancer, medullary thyroid cancer (MTC), breast cancer, and colorectal cancer. Dysregulation of RET contributes to cancer development, highlighting the importance of identifying lead compounds targeting this protein due to its pivotal role in cancer progression. Therefore, this study aims to discover effective lead compounds targeting RET across different cancer types and evaluate their potential to inhibit cancer progression. Methods: This study utilized a range of computational techniques, including phase database creation, high-throughput virtual screening, molecular docking, molecular mechanics with generalized born and surface area solvation (MM-GBSA), assessment of pharmacokinetic properties, and molecular dynamics (MD) simulations, to identify potential lead compounds targeting RET. Results: Initially, a high-throughput virtual screening of the ZINC database identified 2,550 compounds from a pool of 170,269. Subsequent molecular docking studies revealed 10 compounds with promising negative binding scores ranging from -8.458 to -7.791 kcal/mol. MM-GBSA analysis further confirmed the potential of four compounds to exhibit negative binding scores. MD simulations demonstrated the stability of CID 95842900, CID 137030374, CID 124958150, and CID 110126793 with the target receptors. Conclusion: These findings suggest that these selected four compounds have the potential to inhibit phosphorylated RET tyrosine kinase activity and may represent promising candidates for the treatment of various cancers.